Corporate nature : an insider's ethnography of global conservation - Milne, Sarah, 1975- (Critical green engagements., 2022)
"A former conservation insider, Sarah Milne looks inside the black box of mainstream global conservation. Milne finds that corporate behavior and technical thinking dominate conservation practice, while possibilities for ethical conduct and the flourishing of life are constrained"--